A multicentric quality-control study of exercise Doppler echocardiography of the right heart and the pulmonary circulation: the RIGHT Heart International NETwork (RIGHT-NET) - Ferrara, Francesco; Gargani, Luna; Contaldi, Carla; Agoston, Gergely; Argiento, Paola; Armstrong, William F.; Bandera, Francesco; Cademartiri, Filippo; Citro, Rodolfo; Cittadini, Antonio; Cocchia, Rosangela; D’Alto, Michele; et al. (Cardiovascular ultrasound, 2021)
This study was a quality-control study of resting and exercise Doppler echocardiography (EDE) variables measured by 19 echocardiography laboratories with proven experience participating in the RIGHT Heart International NETwork.
Gesehen am 07.05.2022